Colisão de direitos fundamentais e aplicação do princípio da proporcionalidade nas relações de trabalho - Briancini, Valkiria (My University, 2014)
The employment relationships are formed by two subjects, on the one hand the employer, which through the directive power has the right to direct, organize, supervise the installment of the service of the employee; of another, the employee, legally subordinate to the employer. However, the directive power of the employer is not absolute, but it is limited by the presence of the fundamental rights of the employee (eg fundamental right to privacy, non-discrimination), which have effectively in the sphere of labour relations. Thus, the study has as its object the collision of fundamental rights in the employment relations between the directive power of the employer and the fundamental rights of the employee. In the case of collision of these rights the solutions presented in individual cases must always seek to harmonise the areas of tension between the constitutional requirements to achieve, trying to maintain the unity of the Constitution. This way, in these situations the interpreter / applicator of the right uses the method of the balance of goods and the principle of proportionality and its subprinciples, as a means of interpretation, application and as a way of balance in situations of tension and conflict between constitutionally protected rights, which by constitutional rules that they do not have hierarchy between them, as noted in the study topic held in some decisions of the Superior Labour Court on collision of fundamental rights and directive power.
As relações de trabalho são formadas por dois sujeitos, de um lado o empregador, que através do poder diretivo tem o poder de dirigir, organizar, fiscalizar a prestação do serviço do empregado; de outro, o empregado, subordinado juridicamente ao empregador. No entanto, o poder diretivo do empregador não é absoluto, mas sim é limitado pela presença dos direitos fundamentais do empregado (e.g. direito fundamental à intimidade, a vida privada, à não-discriminação), que possuem eficácia na esfera das relações de trabalho. Assim, o estudo tem por objeto a colisão de direitos fundamentais nas relações de trabalho entre o poder diretivo do empregador e os direitos fundamentais do empregado. Nos casos de colisão desses direitos as soluções apresentadas nos casos concretos devem sempre procurar harmonizar as espaços de tensão entre as normas constitucionais a concretizar, procurando manter a unidade da Constituição. Para tanto, nestas situações o intérprete/aplicador do direito emprega o método da ponderação de bens e o princípio da proporcionalidade e de seus subprincípios, como meio de interpretação, aplicação e como forma de sopesamento nas situações de tensão e conflito entre bens constitucionalmente protegidos, que por se tratarem de normas constitucionais não se cogita de hierarquia entre ambas, conforme se constata no estudo tópico realizado em algumas decisões do Tribunal Superior do Trabalho sobre colisão de direitos fundamentais e poder diretivo.
Keywords: Direito do trabalho; Direito do trabalho; Relações trabalhistas; Princípio da proporcionalidade; Direitos fundamentais; Poder diretivo; Colisão; Collision; Directive power; Fundamental rights; Principle of the proportionality; Labor relations; Labor law